The effect of specific chicken based renal diet as monotherapy on clinical, biochemical, urinary and serum oxidative stress parameters in cats with CKD stage 1 and 2 - Krofič, Martina (Slovenian veterinary research, 2023)
The aim of the study was to investigate the effect of a therapeutic renal diet on selected clinical, biochemical, and urinary parameters and on selected parameters of oxidative stress in cats with early stages of chronic kidney disease (CKD). A prospective study of a 3-month duration was conducted to evaluate the effect of renal diet on selected clinical and laboratory parameters in client-owned cats with early stages of CKD. Of a total of 29 enrolled client-owned cats, nineteen (19) cats completed the study, ten receiving renal diet and nine receiving a diet of the owner’s choice. A clinical examination was performed, and blood and urine samples were collected on the day of presentation and at regular check-ups after 3-4, 7-8, and 10-12 weeks. Serum creatinine and symmetric dimethylarginine (SDMA) concentrations and selected parameters of oxidative stress (plasma glutathione peroxidase (GPX) activity and plasma malondialdehyde (MDA) and serum selenium concentrations), were measured and electrophoresis of urinary proteins was performed. At inclusion, a significant positive correlation (p < 0.001) was found between serum selenium concentration and plasma GPX activity (Pearson correlation coefficient 0.83 (95% CI: 0.65 - 0.92) and a significant negative correlation (p < 0.001) between serum SDMA and urine specific gravity (Pearson correlation coefficient -0.70 (95% CI: -0.87 - (-0.38)). At the end of the 3-month feeding trial no significant difference was found in SDMA and creatinine concentrations.